Effect of neutron irradiation on non-equilibrium HfB₂-B₄C composites - Totsky, I.M.; Shynkarenko, V.V.; Popov, O.Yu.; Makara, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We studied the effect of neutron irradiation on composite material HfC-HfB₂- C made using rapid reactive hot pressing technology. The histograms of microhardness and results of X-ray phase analysis, obtained both before and after neutron and electron irradiation of the samples, were considered. It was found that secondary electrons make a considerable contribution at low-fluence (~10¹⁴ neutron/cm² ) neutron irradiation. Afluence range was determined at which reduction of composite material microhardness is observed.